A comparison of sampling methods for seawater microplastics and a first report of the microplastic litter in coastal waters of Ascension and Falkland Islands. (December 2018) - Green, Dannielle S.; Kregting, Louise; Boots, Bas; Blockley, David J.; Brickle, Paul; da Costa, Marushka; Crowley, Quentin
Abstract: To date there is no gold standard for sampling microplastics. Zooplankton sampling methods, such as plankton and Neuston nets, are commonly used to estimate the concentrations of microplastics in seawater, but their ability to detect microplastics is limited by their mesh size. We compared different net-based sampling methods with different mesh sizes including bongo nets (>500 μm), manta nets (>300 μm) and plankton nets (>200 μm and >400 μm) to 1 litre bottle grabbed, filtered (0.45 μm) samples. Concentrations of microplastics estimated using net-based methods were ~3 orders of magnitude less than those estimated by 1 litre grab samples. Some parts of the world with low human populations, such as Ascension Island and the Falkland Islands, lack baseline data on microplastics. Using the bottle grab sampling method we found that microplastic litter was present at these remote locations and was comparable to levels of contamination in more populated coastal regions, such as the United Kingdom. Highlights: Plankton-, bongo- and manta nets underestimate concentrations of microplastics. Sampling with 1 litre bottles is more effective for capturing smaller microplastics. Sampling methods with nets are more effective at capturing larger microplastics. Microplastics are also common in coastal waters of remote location.